2010
DOI: 10.3324/haematol.2010.033514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel fusion, SQSTM1-ALK, in ALK-positive large B-cell lymphoma

Abstract: especially for refractory cases. SQSTM1-ALK may be a rare fusion, but our data provide novel biological insights and serve as a key for the accurate diagnosis of this rare lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 23 publications
(16 reference statements)
1
58
0
Order By: Relevance
“…2D). The coiled-coil domain is shared in all ALK fusion partners (except for NPM, MSN, and SQSTM1), with which the ALK fusion proteins homodimerize leading to constitutive activation of ALK kinase domains (8,19). As expected, in the present study, the oncogenicity of PPFIBP1-ALK was clearly confirmed with an in vitro focus formation assay and an in vivo tumorigenicity assay.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2D). The coiled-coil domain is shared in all ALK fusion partners (except for NPM, MSN, and SQSTM1), with which the ALK fusion proteins homodimerize leading to constitutive activation of ALK kinase domains (8,19). As expected, in the present study, the oncogenicity of PPFIBP1-ALK was clearly confirmed with an in vitro focus formation assay and an in vivo tumorigenicity assay.…”
Section: Discussionsupporting
confidence: 69%
“…1-10), ALK has further been found to generate fusions in inflammatory myofibroblastic tumor (IMT; TPM3, TPM4, CLTC, CARS, RANBP2, ATIC, or SEC31L1; refs. [10][11][12][13][14][15], ALK-positive large B-cell lymphoma (CLTC, NPM, SEC31L1, or SQSTM1; [16][17][18][19], lung cancer (EML4 or KIF5B; refs. 20,21), and ALK-positive histiocytosis (TPM3; ref.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Activated ALK, usually in the form of highly expressed chimeric oncoproteins, is the main oncogenic driver of these neoplasms, which are hence sensitive to therapeutic inhibition with ALK-specific small molecule inhibitors. 26 Epithelioid fibrous histiocytoma is a benign tumor, which virtually always pursues an indolent clinical course; however, the extremely rare occurrence of metastasis of morphologically benign fibrous histiocytoma has been described in one case showing epithelioid morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleophosmin (NPM)anaplastic lymphoma kinase (ALK) fusion protein was first identified as a neoplastic agent in patients with anaplastic large cell lymphoma (ALCL) [Shiota and Mori, 1996;Shiota et al 1995;Morris et al 1994], with the NPMALK protein resulting from the translocation t(2,5)(p23:q35), between the ALK gene on chromosome 2 and the NPM gene on chromosome 5 [Lamant et al 1996;Shiota and Mori, 1996]. ALK has since been linked with many different fusion partners in different tumor types, including TRK-fused gene (TFG), tropomyosin (TPM)3, TPM4, 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase (ATIC), and moesin (MSN) in ALCL; TPM3, TPM4, cysteinyl tRNA synthetase (CARS), Ranbinding protein 2 (RANBP2), and clathrin heavy chain gene (CLTC) in inflammatory myofibroblastic tumor; a variety of ALKamplifying point mutations in neuroblastoma; TPM4 in esophageal squamous tumor; SQSTM1ALK fusion, CLTC, and NPM in diffuse large B-cell lymphoma; and echinoderm microtubule-associated protein-like 4 (EML4) and kinesin family member 5B (KIF5B) in NSCLC [Takeuchi et al 2011[Takeuchi et al , 2009Palmer et al 2009;Webb et al 2009;Mossé et al 2008;Coffin et al 2007;Rikova et al 2007;Soda et al 2007;Jazii et al 2006;Li et al 2004;Ma et al 2003;Onciu et al 2003;Gascoyne et al 2003;Drexler et al 2000]. A further solid tumor ALK fusion (VCLALK in renal cell carcinoma) has also recently been reported [Debelenko et al 2011].…”
Section: Introductionmentioning
confidence: 99%